Interaction between FOG-1 and the Corepressor C-Terminal Binding Protein Is Dispensable for Normal Erythropoiesis In Vivo - Katz, Samuel G. (American Society for Microbiology, 2002)
The hematopoietic, zinc-finger protein FOG-1 is essential for the development of the erythroid and megakaryocytic lineages. FOG-1's function in hematopoiesis is dependent on its ability to interact with the transcription factor GATA-1. FOG-1 has also been observed to interact with the corepressor molecule C-terminal binding protein (CtBP) through a peptide motif shared by all FOG family members. In this study, we confirmed that FOG-1 and CtBP interact by coimmunoprecipitation. We further demonstrate that a FOG-1 mutant unable to interact with CtBP has increased erythropoietic (but not megakaryocytic) rescue (relative to the wild type) of a FOG-1(−/−) cell line. To analyze further the physiological role of the FOG-1-CtBP interaction, we generated knock-in mice that express a FOG-1 variant unable to bind CtBP. Surprisingly, these mice are normal and fertile. Furthermore, erythropoiesis at all stages of development is normal in these mice. Erythrocyte production is similar in mutant and wild-type mice even under conditions of erythropoietic stress stimulated by either exogenously added erythropoietin or phenylhydrazine-induced anemia. Thus, despite conservation of the FOG-CtBP interaction site, the in vivo function of FOG-1 in erythroid development is not affected by its inability to interact with the corepressor CtBP.